Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/8328077
|View full text |Cite
|
Sign up to set email alerts
|

Types, Risk Factors, Consequences, and Detection Methods of Train Driver Fatigue and Distraction

Abstract: Train drivers’ inattention, including fatigue and distraction, impairs their ability to drive and is the major risk factor for human-caused train accidents. Many experts have undertaken numerous studies on train driver exhaustion and distraction, but a systematic study is still missing. Through a systematic review, this work aims to outline the types, risk factors, consequences, and detection methods of train driver fatigue and distraction. The effects of central nervous fatigue and cognitive distraction in tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…(ECG). These methods can describe the drivers' condition with high accuracy, but these methods require a tool that is attached to a certain body part, so it could interfere with the movement while working (Fan et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…(ECG). These methods can describe the drivers' condition with high accuracy, but these methods require a tool that is attached to a certain body part, so it could interfere with the movement while working (Fan et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the high occurrence rate of rail accidents and the resulting socioeconomic consequences in today's world, it is necessary to pay more attention to possible causes or effective factors. Studies have shown that human factors are among the most important factors affecting these accidents (36,37). This issue becomes much more important considering the rights of each individual to have health and satisfaction in life.…”
Section: Discussionmentioning
confidence: 99%
“…In Cognitive Ergonomics, "attention" is treated as a single resource or multiple resources that are utilized during human information processing. Driver inattention can be classified into two main types [4], including distraction and mental fatigue [5]. Attention can be disrupted in a variety of ways.…”
Section: A Driver Distraction and Its Typesmentioning
confidence: 99%